Pengembangan Website Tracer Study untuk Mendukung Evaluasi Mutu Pendidikan Tinggi di Institut Bisnis IT&B Menggunakan Metode V-Model - Andi; Rezeki Ongsa Ong (JURNAL PENDIDIKAN & PENGAJARAN (JUPE2), 2026)
Higher education institutions play an important role in producing qualified graduates and continuously evaluating alumni outcomes as part of educational quality improvement. One approach to support this process is the implementation of a tracer study through an integrated information system. This study aims to develop an alumni Tracer Study website for Institut Bisnis IT&B using the V-Model development methodology to support alumni data management and provide information for institutional evaluation. The V-Model was selected because it incorporates verification and validation activities throughout each stage of software development, resulting in a reliable system that meets user requirements. The developed website provides features including alumni registration, tracer study questionnaires, alumni search, job vacancy information, graphical data visualization, and career report generation. The results indicate that the developed website improves the effectiveness of alumni data management and supports educational quality evaluation at Institut Bisnis IT&B. User Acceptance Testing (UAT) involving 30 respondents produced an average acceptance score of 94.9%, indicating that the system is highly feasible for implementation as a tracer study platform and as a decision-support tool for curriculum development and educational quality enhancement.